Evaluation of miR-146a as a potential biomarker for diagnosis of cardiotoxicity induced by chemotherapy in patients with breast cancer - Nasrin Zare; Nasim Dana; Azam Mosayebi; Golnaz Vaseghi; Shaghayegh Haghjooy Javanmard (Journal of Research in Medical Sciences)
Background: Cardiotoxicity from chemotherapy may result in cardiomyopathy and heart failure. Clinicians can use the evaluation of cardiotoxicity-specific biomarkers, such as microRNA, as a tool for the early detection of cardiotoxicity. The study’s objective was to assess miR-146a levels as a potential biomarker for the detection of cardiotoxicity brought on by chemotherapy in patients with breast cancer. Materials and Methods: Using quantitative reverse transcription-polymerase chain reaction, the levels of miR-146a were assessed in the blood of 37 breast cancer patients receiving anthracyclines without cardiotoxicity and 33 breast cancer patients experiencing cardiotoxicity brought on by chemotherapy after chemotherapy. Left ventricular ejection fraction (LVEF) ≥50% was used to define heart failure by echocardiography. Results: MiR-146a did not show any significant difference in expression between these two study groups (P = 0.48, t-test). The expression level of miR-146a was not significantly associated with LVEF, age, and body mass index (P > 0.05), according to Pearson correlation. Conclusion: MiR-146a may be a diagnostic or prognostic biomarker for cardiotoxicity brought on by chemotherapy, even though there was no discernible difference in the expression level of miR-146a between the control group and the breast cancer patients who were experiencing this side effect of chemotherapy. Therefore, miR-146a expression needs to be examined in a sizable cohort of breast cancer patients who are experiencing cardiotoxicity brought on by chemotherapy.